Process Analysis of A Public Policy in Turkey: Medical Tourism - Kantaş Yılmaz, Fatma; Çapar, Haşim; Şeker, Canan (Süleyman Demirel Üniversitesi, 2021)
Medical tourism field, which is a developing industry in terms of variety and popularity of medical interventions, generated inthe formation of policy, implementation, understanding the efficiency and effectiveness would help to build Turkey's futureprojections. The purpose of the research is to analyze the policy of medical tourism in Turkey in the context of actors by using“Process Analysis Model”. In the study which is designed with qualitative method, case study design and purposive samplingmethods are used. The findings are analyzed by content analysis method under the headings of the model: agenda setting,formulation, legitimation, implementation and evaluation. The common opinion that the actors of medical tourism do not fullyutlise the potential of medical tourism potential in Turkey, underlines the importance of enhancing the participation andcollaboration of stakeholders in increasing the market share in Turkey.

Tıbbi müdahalelerin çeşitliliği ve popülerliği bakımından gelişmeye devam eden bir endüstri olan medikal turizm alanında üretilen politikaların oluşturulmasını, uygulanmasını, değerlendirilmesi, etkinliği ve etkililiğini anlamak; hiç şüphesiz ki Türkiye’nin gelecek projeksiyonlarının oluşturulmasına yardımcı olacaktır. Bu araştırmanın amacı, Türkiye’de medikal turizm politikalarını, aktörler bağlamında “Süreç Analiz Modeli” kullanılarak analiz etmektir. Bilimsel araştırma yöntemlerinden nitel yöntemle tasarlanan bu araştırmada, durum çalışması deseni ve amaçlı örnekleme yöntemleri kullanılmıştır. Çalışmadan elde edilen bulgular içerik analizi yöntemi ile Süreç Analiz Modelinde yer alan başlıklar altında ele alınmıştır. Bu başlıklar; gündeme geliş, formüle ediliş, kanunlaştırma, uygulama ve değerlendirmedir. Çalışma yapılırken medikal turizme taraf olan aktörlerin medikal turizm potansiyelimizi yeterince kullanamadığımız yönündeki ortak görüşü, Türkiye’nin medikal turizm alanındaki pazar payının arttırılmasında paydaşların katılım ve iş birliğinin öneminin altını çizmektedir.
TÜRKİYE’DE BİR KAMU POLİTİKASI SÜREÇ ANALİZİ: MEDİKAL TURİZM
JEL Classification Codes: I18 / JEL Sınıflandırma Kodları: I18.
Keywords: Politics; Turkey; Türkiye; Medical tourism; Process analysis; Politika; Türkiye; Medikal turizm; Süreç analizi